Specialty Grand Challenge: Wherever Tourism Arrives, Society Notes It First! - Schänzel, Heike; Apollo, Michal (Frontiers Media, 2023)
Sustainability research in tourism increasingly focuses on social issues such as the relationship between residents’ quality of life and the positive experiences/outcomes of tourists (Helgadóttir et al., 2019). To fully harness the power and opportunities of bringing people and communities together the UNWTO Global Code of Ethics for Tourism (www.unwto.org/global-code-of-ethics-for-tourism) was developed as a reference point for responsible and sustainable tourism. Adopted in 1999 by the World Tourism Organization, the Code’s 10 articles are not legally binding and cover the right to tourism, rights of workers and entrepreneurs, and ensuring benefits for host communities amongst other matters. Still, these laudable ideas are not always adhered to, even by their initiator, the UNWTO. In a post-pandemic environment and more than two decades later, it remains to be established whether any progress relating to social sustainability has been achieved. Tourism is full of paradoxes as highlighted by Hall (2022), and fundamental questions remain on how tourists’ desire for hedonistic joy can simultaneously contribute to the wellbeing of local communities. Or how an emphasis on economic benefits can simultaneously consider the social needs of all stakeholders in the visitor economy. This is the grand challenge that achieving social sustainability of tourism faces.